Application of Fecal Volatile Organic Compound Analysis in Clinical Practice: Current State and Future Perspectives - Sofia el Manouni el Hassani; Daniel J. C. Berkhout; Sofie Bosch; Marc A. Benninga; Nanne K. H. de Boer; Tim G. J. de Meij (Chemosensors, 2018)
Increasing interest is noticed in the potential of volatile organic compound (VOC) analysis as non-invasive diagnostic biomarker in clinical medical practice. The spectrum of VOCs, originating from (patho)physiological metabolic processes in the human body and detectable in bodily excrements, such as exhaled breath, urine and feces, harbors a magnificent source of information. Thus far, the majority of studies have focused on VOC analysis in exhaled breath, aiming at identification of disease-specific VOC profiles. Recently, an increasing number of studies have evaluated the usability of VOC present in the headspace of feces in the diagnostic work-up of a wide range of gastrointestinal diseases. Promising results have been demonstrated particularly in those diseases in which microbiota alterations are considered to play a significant etiological role, such as colorectal carcinoma, inflammatory bowel disease, irritable bowel syndrome, celiac disease and infectious bowel diseases. In addition, fecal VOC analysis seems to have potential as a diagnostic biomarker for extra-intestinal diseases, including bronchopulmonary dysplasia and sepsis. Different methods for VOC analysis have been used in medical studies, such as gas-chromatography mass spectrometry, selected-ion flow tube-mass spectrometry, ion-mobility spectrometry, and electronic nose devices. In this review, the available literature on the potential of fecal VOCs as diagnostic biomarker, including an overview of relevant VOC detection techniques, is discussed. In addition, future hurdles, which need to be taken prior to implementation of VOC analysis in daily clinical practice, are outlined.